Rekonstruksi Makna Kerukunan dalam Etika Islam Jawa Menurut Perspektif Franz Magnis Suseno - Rafsanjani, Ali Ramadhan (Javano Islamicus, 2023)
Human life is inevitably marked by potential social conflicts that threaten harmony. Within the framework of Javanese culture, the value of kerukunan (social harmony) represents a moral ideal embodied in the principle of dunia tentrem a peaceful, balanced, and respectful mode of living. This ideal resonates strongly with Javanese Islamic ethics, which emphasizes akhlaqul karimah (noble character), respect for others, and self-restraint as pathways toward social peace. This study aims to explore the meaning of kerukunan within Javanese ethics from the perspective of Franz Magnis Suseno and to relate it to the values of Javanese Islamic ethics embedded in local traditions. Using a qualitative approach with a descriptive-analytical method, the data were obtained from Suseno’s works and relevant literature on Islamic ethics and Javanese culture. The analysis employed deductive and inductive reasoning to reveal the philosophical relationship between these ethical systems. The findings indicate that the principles of harmony and respect in Javanese ethics align with Islamic teachings on adab (proper conduct), politeness, and tasamuh (tolerance). This study concludes that Javanese Islamic ethics represents a harmonious synthesis between Islamic spirituality and indigenous moral wisdom.